2021
DOI: 10.3390/diagnostics11091721
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Early Mycosis Fungoides

Abstract: Mycosis fungoides (MF), the most common type of cutaneous T-cell lymphomas, generally has a favorable clinical course. Early MF typically presents erythematous patches and/or plaques and lasts for many years without affecting the life expectancy. Only limited cases progress to develop skin tumors, with subsequent lymph nodes and rarely visceral organ involvement. One of the clinical problems in early MF is the difficulty in differentiating the disease from benign inflammatory disorders (BIDs), such as atopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…On the other hand, loss of pan T-cell markers, such as CD2, CD5, and CD3 is more specific for MF, but rarely occurs in the early stages. It is noteworthy to mention that the best assessment of immunophenotypic alterations should be at the epidermal lymphocytes, as the number of lymphoma cells in the dermis is low in early MF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, loss of pan T-cell markers, such as CD2, CD5, and CD3 is more specific for MF, but rarely occurs in the early stages. It is noteworthy to mention that the best assessment of immunophenotypic alterations should be at the epidermal lymphocytes, as the number of lymphoma cells in the dermis is low in early MF [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increased CD4:CD8 ratio is more evident in advanced-stage MF, but it may be inconspicuous in early-patch-stage MF lesions, and the loss of CD7 expression can also be observed in various inflammatory dermatoses, including parapsoriasis. A substantial loss of CD7 expression (CD7 + < 10% of infiltrating lymphocytes) is more specific to MF, with 41–80% sensitivity and 93–100% specificity, according to a previous report [ 22 ]. For these reasons, physicians may not be able to distinguish parapsoriasis from early-stage MF on the basis of only clinicopathological and immunohistochemical grounds.…”
Section: Association With Lymphomamentioning
confidence: 81%
“…In an attempt to differentiate MF from inflammatory skin diseases, in 2005, the International Society for Cutaneous Lymphoma proposed an algorithm for diagnosing early-stage MF using a 4-point scoring system. It comprised clinical, histologic, immunophenotypic, and molecular criteria [ 22 , 28 ]. Later, several studies evaluating the validity and reliability of the algorithm showed that it was very sensitive but not very specific for diagnosis MF (87.5–100% sensitivity, 60% specificity) [ 22 ].…”
Section: Association With Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have sought out to histologically analyze MF in skin of color; classic MF in skin of color was described as an atypical, epidermotropic T-cell infiltrate; as an atypical lymphoid infiltrate that stained positive for CD8+ in hypopigmented MF; as a band-like infiltrate in the surficial dermis with intrafollicular atypical T-cells in folliculotropic MF; and as epidermal hypoplasia, hyperkeratosis with Pautrier microabscesses in verrucous MF (Nakamura et al, 2021). In immunohistochemical analysis of MF, tumor cells stain positively for CD3 and CD4 but negatively for CD8 (Miyagaki, 2021). Diagnosis of MF can also be suggested by a ratio of CD4/CD8 cells of greater than 4–6.…”
Section: Dermatopathologymentioning
confidence: 99%